Analisis Sentimen Perubahan Harga Emas Dunia, Nilai Tukar Rupiah dan Indeks Harga Saham Gabungan terhadap Keputusan Membeli Produk Reksadana Saham - Parengkuan, Frangky Christoffel (Jurnal Ilmiah Magister Managemen)
The objective of this study are (1) to describe the exchange of world gold price, USD/IDR exchage rate, the movement in Indonesian Stocks Exchange Indexs (IHSG) and investor’s sentiment to buy Equity Fund (2) to verify the corelation against the world gold price, USD/IDR exchange rate and movement of Indonesian Stocks Exchange Indexs (3) to calculate how they will make effect to decision of buying Equity Fund. The Equity Funds come from all funds that sold by Bank Danamon Region 8 Jawa Barat with minimum existing for more than 10 years performance. Analytical tools that used in this study is path analysis with two statistical methods. The result showed that even in LISREL and SPSS the correlation between world gold prices and USD/IDR Exchange Rate is too low, but correlation between world gold prices and IHSG is strong enough. The strongest coorelation is on USD/IDR exchange rate and IHSG. When it is tested in path analysis, the result shows that all independent variabel have significant effect to investor sentiment of buying Equity Fund.